Recognition of Economic Growth Sources with Institutionalized Economics Approach - Barekat, Gholamhossein; Moradi, Ali (International Journal of Economics and Financial Issues, 2018)
Nowadays, achievement of high economic growth is the main purpose of all economic firms and is also the focus point of all activities taken to have supervision on economic affairs of developed countries. At the same time, the institutionalized approach has been applied to analyze the nature of poverty and wealth of nations. Some economists believe that institutions play vital role in economic growth of countries, especially developing countries. Institutional environment is one of the most important elements of institutional structure framework forming an economic system. An economic system can be established and continued based on an institutional environment. In fact, institutional environment can provide the play rules for governmental mechanism and also for the market mechanism and can also determine the structure of relations between the government and market in an economic system. In addition to government and market, economic system encompasses also another underlying element called institutional environment. According to relations of institutional indices with other, analysis of separate effect of institutional indicators on economic growth is difficult. Hence, the applied method in this study proposes a set of institutional indicators in frame of institutional environment. This study has applied institutionalized economics approach with the definition of institutional factors of economic freedom, judicial system and bureaucracy level as institutional environment. Moreover, the study has applied developed criterion of institutional quality (IQ) and has analyzed the economic performance and has taken descriptive analysis and applied econometrics patterns and panel data. The results obtained from the study show that if the institutional environment shows the expected performance, it can leave positive effects on economic performance. Institutional factor of judicial system has direct and positive effect on economic growth and the effect of institutional factor of bureaucracy and overall freedom index on economic growth was not confirmed in this study. Keywords: institutional environment, economic growth, institutionalized economics, institutional quality, judicial system, bureaucracy JEL Classifications: D73, EO2, F43